2014
DOI: 10.1111/ede.12061
|View full text |Cite
|
Sign up to set email alerts
|

The lateral mesodermal divide: an epigenetic model of the origin of paired fins

Abstract: By examining development at the level of tissues and processes, rather than focusing on gene expression, we have formulated a general hypothesis to explain the dorso-ventral and anterior-posterior placement of paired appendage initiation sites in vertebrates. According to our model, the number and position of paired appendages are due to a commonality of embryonic tissue environments determined by the global interactions involving the two separated layers (somatic and visceral) of lateral plate mesoderm along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Finally, it has been suggested that developing paired appendages and hindgut are associated in more ways than shared Hox expression patterns. Several key innovations following the two rounds of genome duplications in the stem lineage of vertebrates allowed for both the regionalization of the gastrointestinal tract and the emergence of paired appendages from the somatopleure in jawed vertebrates [ 51 53 ]. We demonstrate that HoxA DP expression is utilized to differentially pattern the distal gut, in a fashion that is reminiscent of what has been observed in the distal region of paired appendages.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it has been suggested that developing paired appendages and hindgut are associated in more ways than shared Hox expression patterns. Several key innovations following the two rounds of genome duplications in the stem lineage of vertebrates allowed for both the regionalization of the gastrointestinal tract and the emergence of paired appendages from the somatopleure in jawed vertebrates [ 51 53 ]. We demonstrate that HoxA DP expression is utilized to differentially pattern the distal gut, in a fashion that is reminiscent of what has been observed in the distal region of paired appendages.…”
Section: Resultsmentioning
confidence: 99%
“…As for the epaxial–hypaxial differentiation, paired fins are a useful indicator. In gnathostomes, paired appendages with mesodermal contributions (muscles and endoskeleton) require ( i ) primaxial–abaxial differentiations bordered by the lateral somitic frontier and ( ii ) dorsoventral compartmentalization within the abaxial domain and in the ectoderm (Nowicki, Takimoto & Burke, ; Johanson, ; Onimaru et al ., ; Tulenko et al ., ; de la Rosa, Müller & Metscher, ). These polarities in embryonic tissues largely correspond to the adult epaxial–hypaxial distinction (epaxial: mainly derived primaxially; hypaxial: mainly derived abaxially).…”
Section: Mandibular Confinement Hypothesismentioning
confidence: 99%
“…Accordingly, in the last years various authors have postulated evolutionary models based on/supporting the fin‐fold theory. For instance, Nuno de la Rosa et al, 64 based on a developmental analysis focused on tissues and processes, proposed a model to explain the dorsoventral and anterior‐posterior placement of paired appendage initiation sites. For them, the number and position of these appendages are the result of a commonality of embryonic tissue environments determined by global interactions involving the somatic and visceral layers of lateral plate mesoderm within the embryonic dorsoventral and anterior‐posterior portion of the body.…”
Section: Support For Fin‐fold Theory Vs For Gegenbaur's Theorymentioning
confidence: 99%